Borys Antonenko-Davydovych as the fighter for the standardization of the Ukrainian language (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
A survey article dealing with the life work of the Ukrainian writer and translator B. Antonenko-Davydovych. Special attention is paid to his linguistic publications on matters relating to proper Ukrainian usage from the second half of the 20-th century.
Keywords: B. Antonenko-Davydovych; proper usage; Standard Ukrainian; classical tradition; living language of the people